One‐Pot Synthesis and Biological Evaluation of Arylpropenone Aminochalcone Conjugates as Potential Apoptotic Inducers. Issue 16 (25th April 2019) - Khan, Irfan; Ganapathi, Thipparapu; Shareef, Mohd Adil; Shaik, Anver Basha; Akbar, Syed; Rajanna, Ajumeera; Kamal, Ahmed; Kumar, Chityal Ganesh
Abstract: A facile single pot strategy was developed to synthesize a library of 17 arylpropenone aminochalcone conjugates involving two consecutive reactions, namely Michael addition and Claisen‐Schmidt condensation. These conjugates were screened for their in vitro anti‐proliferative potential against selected human cancer cell lines such as breast (MCF‐7 and MDA‐MB‐231), pancreatic (PANC‐1) and colorectal (CaCO2) adenocarcinoma cells. Among them, the conjugates 6 l and 6p exhibited good to moderate cytotoxicity with IC50 values ranging from 6.7 μM and 9.8 μM, respectively, against MCF‐7. Furthermore, these conjugates were found to exhibit G0/G1 cell cycle arrest. Moreover, Annexin‐FITC assay revealed that they induced apoptosis in a dose‐dependent manner which probably is responsible for their Cytotoxicity Abstract : A library of 17 arylpropenone aminochalcone conjugates were designed, synthesized in one pot manner and investigated for their in vitro antiproliferative activity. Among them, the conjugates 6 l and 6 p showed good to moderate cytotoxicity with IC50 values of 6.7 μM and 9.8 μM, respectively, against MCF‐7 (human breast cancer cell line). While, Annexin‐FITC assay revealed that they induced apoptosis in a dose‐dependent manner which is responsible for their cytotoxicity.